Integrated Procurement-Production Inventory Model with Two-Stage Production - Dana Marsetiya Utama; Heri Mujayin Kholik; Azis Fredy Mulya (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
The inventory-production system concerns the effective management of the goods flows from raw materials to finished products. The Integrated Procurement-Production (IPP) system consists of many elements that must be managed effectively. The problem will be more complex if it involves deciding on the number of delivery frequencies at the retailer level. In this case, the Integrated Procurement-Production's objective function depends on the frequency of raw material shipments, the frequency of delivery of finished products, and the production cycle time. This study aims to develop an IPP system to maximize total profit. The decision variables used are the frequency of raw material delivery, the frequency of delivery of finished products, and the production cycle time. This study proposes the Dragonfly Algorithm (DA) as an algorithm for problem-solving. Dragonfly Algorithm is used to find the best inventory decision variables. This study conducted experiments with various iteration parameters and DA population. The results showed that the greater the iteration and the population used, the greater the profit. A sensitivity analysis of decision variables is also presented in this investigation.